(untitled) (Research, Society and Development, 2022)
Urinary tract infection (UTI) and urinary tract colonization are extremely frequent, occurring in all age groups. The indiscriminate use of antibiotics in outpatient settings, and also in the nosocomial environment, is an important risk factor for the emergence and spread of microbial resistance. The high level of multiple resistance presents a potential risk to public health and can make it difficult to treat diseases. We analyzed the bacterial resistance profile of urine cultures, as well as data on urinary infections and urinary tract colonization in patients treated at the Intensive Care Unit (ICU) of Fundação Hospitalar São Lucas, in Cascavel/PR. This is a cross-sectional, retrospective study, carried out through medical records of patients admitted to an intensive care unit, from January 2019 to January 2021. We analyzed data on urinary tract infection and urinary tract colonization, as well as profile of microbial resistance and clinical characteristics of the respective patients. We obtained a total of 87 patients who had a positive urine culture, 66 of which were urinary tract colonizations, 9 classified as non-catheter-associated UTI, 10 as catheter-associated UTI and 2 as healthcare-related UTI. We found 15 types of microorganisms and different antibiotic resistances. We compared it with 4 other works, to get the difference in resistance values ​​in different locations. The bacteria most found in the study were Escherichia coli, Klebsiella sp. and Pseudomonas aeruginosa. Pseudomonas aeruginosa had the highest percentages of multidrug-resistant isolates.